2019
DOI: 10.20524/aog.2019.0443
|View full text |Cite
|
Sign up to set email alerts
|

Proximal esophageal contraction after induction of ineffective distal contraction by sildenafil in healthy volunteers

Abstract: Background Proximal esophagus is composed of striated muscle replaced by smooth muscle in the distal section. Sildenafil, an inhibitor of phosphodiesterase type 5, causes a decrease in the amplitude of contractions in distal smooth muscle esophagus, with no effect on the proximal esophageal striated muscle. The aim of this investigation was to evaluate the hypothesis that proximal contractions are affected by changes in distal contractions caused by sildenafil. Methods Esophageal motility was assessed by high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The included studies were published between 2000 and 2021. The study by Costa, T. (2020) was conducted in Brazil and had the largest sample size with 22 patients [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The included studies were published between 2000 and 2021. The study by Costa, T. (2020) was conducted in Brazil and had the largest sample size with 22 patients [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…The LES residual pressure values were not significantly different between the sildenafil and placebo groups at the post-infusion period. In the Brazilian study [ 15 ] it was demonstrated a significant increase in proximal and also distal contractile integral after sildenafil intake. Contractile integral was defined as the amplitude of contraction * duration of contraction * length of contraction.…”
Section: Discussionmentioning
confidence: 99%